Upaya pengurangan potensi banjir pada kawasan karst melalui pembelajaran kontekstual berbasis lingkungan pada siswa SMA - Fahmi, Muhammad Rizieq; Sumarmi, Sumarmi; Rizal, Syah; Marlina, Marlina (Universitas Negeri Malang, 2025)
Efforts to reduce flood potential in karst areas through environment-based contextual learning for high school students MA Darussalam Ngentrong is located in the southern part of Tulungagung Regency. The area has the potential for flooding with high frequency during the rainy season. Therefore, to reduce the risk of flooding, efforts are needed to increase the capacity of disaster knowledge through learning activities in schools. Students need to understand disaster competencies based on the learning resources around them. This community service (PKM) aims to implement contextual learning based on the environment to increase disaster capacity in MA Darussalam Ngentrong. This PKM activity uses a participatory action research (PAR) approach that focuses on active participation from schools. The implementation of this program has three stages: introduction, PKM implementation, and evaluation. The results of this study include the implementation of PKM by implementing contextual learning based on the environment and student participation in planting trees as an implementation of the “one house, one tree” campaign. This program prepares the younger generation to reduce flood risk through knowledge socialization to the community and active participation in environmental restoration activities. MA Darussalam Ngentrong terletak di bagian selatan Kabupaten Tulungagung. Kawasan tersebut berpotensi ancaman banjir dengan frekuensi tinggi pada musim hujan. Maka, sebagai upaya mengurangi risiko bencana banjir, diperlukan usaha untuk meningkatkan kapasitas pengetahuan bencana melalui kegiatan pembelajaran di sekolah. Siswa perlu memahami kompetensi kebencanaan berdasarkan sumber belajar disekitarnya. Tujuan dari pengabdian kepada masyarakat (PKM) ini adalah untuk melaksanakan pembelajaran kontekstual berbasis lingkungan sebagai upaya peningkatan kapasitas kebencanaan di MA Darussalam Ngentrong. Kegiatan PKM ini menggunakan pendekatan penelitian tindakan partisipasi (PAR) yang berorientasi pada partisipasi aktif dari sekolah. Pelaksanaan program ini mempunyai tiga tahap yaitu pendahuluan, pelaksanaan PKM, dan evaluasi. Hasil penelitian ini antara lain pelaksanaan PKM dengan menerapkan pembelajaran kontekstual berbasis lingkungan dan partisipasi siswa dalam penanaman pohon sebagai implementasi kampanye “satu rumah, satu pohon”. Program ini mempersiapkan generasi muda dalam upaya pengurangan risiko banjir melalui sosialisasi pengetahuan kepada masyarakat dan partisipasi aktif dalam kegiatan restorasi lingkungan.